IMPLEMENTASI PENDIDIKAN KARAKTER UNTUK MEMBENTUK KEPRIBADIAN SISWA SEKOLAH DASAR - Rahidatul Laila Agustina (Elementa: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
Implementation of character education in learning must involve all components (stakeholders) in the school environment starting from the curriculum, learning process, handling and management of subjects, school management, and so on to become a school culture so that it underlies the values ​​of behavior, daily habits, symbols - symbols which is practiced by all members of the school so that eventually it forms a good character.